Efficacy of single-dose galcanezumab 240 mg on episodic or refractory chronic cluster headache: prospective, 4-week, real-world evidence from the GRASP study group - Vikelis, Michail; Argyriou, Andreas A.; Chondrogianni, Maria; Foska, Aikaterini; Rikos, Dimitrios; Tsironis, Christos; Soldatos, Panagiotis; Koutsokera, Maria; Dermitzakis, Emmanouil V. (Frontiers in Neurology, 2026)
ObjectiveThis prospective real-world study, conducted by the Greek Research Alliance for the Study of Headache and Pain (GRASP), aimed to evaluate the efficacy, tolerability and safety of subcutaneous galcanezumab 240 mg in reducing the frequency and clinical burden of CH attacks at week 4.MethodsThe primary endpoint was the change in the mean number of daily cluster attacks from baseline to weeks 2 and 4. The co-primary endpoint was the ≥50% response rate at week 4 versus baseline. Secondary endpoints included attack duration, pain intensity (VAS 0-10), quality of life (EQ-VAS), treatment satisfaction (PGIC 1–7), and galcanezumab safety and tolerability, all assessed comparing the outcomes at weeks 2 and 4 with those at the baseline.ResultsForty-seven patients with episodic (eCH, n = 30) or refractory chronic cluster headache (cCH, n = 17) received a total dose of 240 mg of galcanezumab, consisting of two pre-filled 120 mg syringes. Mean age was 43.6 years; 78.7% were male. At week 4, mean daily attacks decreased from 2.6 to 1.2 in eCH (p < 0.001) and from 2.8 to 1.5 in cCH (p = 0.004) with significant effect sizes. A response rate >50% was observed in 63% of patients with eCH and in 65% of patients with cCH. Pain intensity (VAS) and attack duration significantly improved, alongside EQ-VAS quality of life and PGIC satisfaction scores. Adverse events during the galcanezumab treatment were mild and transient, and did not lead to discontinuations.ConclusionA single 240 mg dose of galcanezumab significantly reduced attack frequency, pain, and duration in both patients with eCH and refractory cCH, improved quality of life and patients’ satisfaction, and was well-tolerated. These real-world findings support the use of galcanezumab mostly in eCH, while larger studies are needed to clarify its role in cCH.